Sargassum wightii ameliorates anxiety-like behaviour and cognitive deficits in rotenone-induced parkinsonian rats - Bandana Rath; Lalit Mohan Sika; Ikhita Misra; Snigdha Rani Panigrahy; Baidyanath Mishra (Shahrekord University of Medical Sciences, 2023)
Introduction: Parkinson's disease (PD) is a neurodegenerative disorder, basically manifested by motor symptoms. However, there are other associated non-motor features in PD, including depression, anxiety, and cognitive impairments that significantly affect the quality of life. Scientific reports have shown that Sargassum wightii, a brown seaweed, protects against rotenone-induced motor deficits, mitochondrial dysfunction, and oxidative stress in rats. We therefore, undertook this study to evaluate its efficacy in alleviating rotenone-induced non-motor symptoms such as anxiety-like behavior and cognitive deficits in rats. Methods: Rotenone at a dose of 10 mg/kg was given orally for 28 days to induce PD model in male rats. The vehicle and the test drug were given orally daily, 1 hour prior to the rotenone administration. The protective effect of S. wightii (methanol extract at 400 mg/kg dosage) was assessed through an array of tests: Elevated plus maze test, Morris water maze test, and novel object recognition test. On the 28th day, the rats were sacrificed, and hippocampal neurobiochemical analyses were performed using high-performance liquid chromatography (HPLC). Results: Co-administration of S. wightii reversed the rotenone-induced anxiety-like behavior and cognitive deficits to a significant extent (P<0.001). It also restored the hippocampal neurotransmitters (5-hydroxytryptamine, dopamine, and 5-hydroxy indole acetic acid) significantly (P<0.001). Conclusion: Sargassum wightii provides neuroprotective effects and reduces the non-motor symptoms of PD. Therefore, it might be a novel insight into PD therapy.